Revisão taxonômica do gênero Bolbapium Boucomont, 1910 (Coleoptera, Scarabaeoidea, Geotrupidae) - Santana, Edrielly Carolinne Carvalho de (2021)
The genus Bolbapium Boucomont 1910 is composed by 22 species distributed in the neotropical region of South America. The presente study brings the taxonomic revision of the genus, from the analysis of external morphological characters and male genitália, including redescripcion of species: Bolbapium baeri (Boucomont, 1902), Bolbapium borgmeieri Martínez, 1976, Bolbapium caesum (Klug, 1843), Bolbapium howdeni Martínez, 1976, Bolbapium lucidulum (Klug, 1843), Bolbapium minutum (Luederwaldt, 1931), Bolbapium modestum (Castelnau, 1840), Bolbapium paralucidulum Ide & Martínez, 1993, Bolbapium parcepunctatum (Arrow, 1913), Bolbapium quadrispinosum (Luederwaldt, 1931), Bolbapium quinquestriatum (Boucomont, 1932), Bolbapium sculpturatum (Mannerheim, 1829), Bolbapium striatopunctatum (Castelnau, 1840), Bolbapium sulcifrons Ide & Martínez, 1993. Description of eight new species were also offered, as well as ilustrations, distribution maps, designation of type material and transfer of Bolboceras modestum to the genus. A synonymy raised earlier in a dissertation is confirmed and is being proposed: Bolbapium minutum Luederwaldt, 1931 = Bolbapium bigibbosum syn.n. Luederwaldt, 1931.